THE VELENJE COAL MINE’S SPATIAL MONITORING OF SURFACE AND STRUCTURE MOVEMENTS - Potočnik, Drago; Rošer Janez; Vulić Milivoj (Journal of Energy Technology, 2024)
The Velenje Coal Mine’s (VCM) system of surface observation is complex and can be classified as an extended geodetic monitoring system. In addition to the standard geodetic techniques (triangulation, trilateration, levelling, GNSS), it also includes more modern methods such as aerophotogrammetry, terrestrial laser scanning and an automatic Real-Time GNSS Deformation Monitoring System. By using the Real-Time GNSS Deformation Monitoring System, we are able to monitor not only the potential impact of mining on the power plant facilities but also the impact of the newly constructed power generating facility, Unit 6, and the combined effects on existing facilities. With an extended geodetic monitoring system, the surface movements and deformations on over 300 measurement points in the Šalek Valley are observed. Furthermore, with sonar measurements, we are determining the Šalek lakes’ bottom surface and performing observations of structure movements and deformations. The extended VCM geodetic monitoring system is constantly being expanded and upgraded with new measurements and the latest equipment.